TRANSFORMASI ETNOSOSIAL SEBAGAI BASIS PENGUATAN PENDIDIKAN INKLUSIF DI SEKOLAH DASAR - Muhammad Agung Nur Huda; Syamsul Hadi; Radeni Sukma Indra Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the forms of ethnosocial transformation in inclusive education practices at the elementary school level, describe the relationship between inclusive education policies and ethnosocial values, and explain the role of ethnosocial transformation in bridging the gap between policy norms and inclusive education practices in elementary schools. The study employed a systematic literature review method using a descriptive qualitative approach with a policy analysis design based on literature review. Data were obtained through document analysis of national education regulations and relevant scholarly articles related to inclusive education and ethnosocial transformation. Data analysis was conducted using thematic content analysis and an interactive analysis model. The findings indicate that ethnosocial transformation in inclusive education at the elementary school level is manifested through changes in perspectives on justice and diversity, the strengthening of social relations and collaboration among school communities, and the transformation of inclusive pedagogical practices and classroom management. These findings affirm that ethnosocial values function as a bridge between policy norms and inclusive education practices; therefore, strengthening inclusive education requires strong policy integration accompanied by the transformation of social values and school culture